Tinkery - Cher, Marilyn Shi Hui (2015)
Beyond mere semantics, the concept of “creativity” is often misunderstood by many. Attempts to nurture creativity from young, therefore, often achieve the contrary – robbing the young of their innate creative possibilities. This study seeks to disabuse lay notions of creativity, exploring practical methods to educate the young while preserving and promoting their innate creative capacity. Cognisant of the boundless applicability of creative process, this study focuses purely on the nurturing of creativity through art.